Clinical features of Cytomegalovirus retinitis in patients with acquired immunodeficiency syndrome and efficacy of the current therapy - Zhao, Qing; Li, Ning-ning; Chen, You-xin; Zhao, Xin-yu (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Cytomegalovirus retinitis (CMVR) is the most common and sight-threatening opportunistic retinal infection in patients with acquired immunodeficiency syndrome (AIDS) and several controversies remain to be settled. We aimed to summarize the current evidence and clarify the clinical features and prognosis of CMVR in AIDS patients. Methods: The databases PubMed, EMBASE, and Ovid from inception to April 2022 were searched to identify the relevant studies. R software version 3.6.3 was used to perform the statistical analyses. Results in proportion with 95% confidence interval (CI) were calculated using the Freeman-Tukey variant of arcsine square transformation. Results: We finally included 236 studies comprising 20,214 patients. CMVR in AIDS was male-dominated (88%, 95%CI 86%-89%), with 57% (95%CI 55%-60%) aged <41 years and 44% (95%CI 41%-47%) being bilaterally involved. CMVR was preponderant in AIDS patients with the following characteristics: white and non-Hispanic, homosexual, HIV RNA load ≥ 400 copies/mL, and CD4+ T-cells <50 cells/μL. The positivity of CMV-DNA in blood, aqueous humor, and vitreous humor was 66% (95%CI 52%-79%), 87% (95%CI 76%-96%), and 95% (95%CI 85%-100%), respectively. The most common symptoms were blurred vision (55%, 95%CI 46%-65%), followed by asymptomatic, visual field defect, and floaters. CMVR was first diagnosed and regarded as the clue to AIDS diagnosis in 9% (95%CI 6%-13%) of CMVR patients. Approximately 85% (95%CI 76%-93%) of the CMVR patients have received cART. CMVR remission was observed in 72%-92% of patients depending on the specific category of anti-CMV therapy. The general incidence of CMVR-related RD in the entire course was 24% (95%CI 18%-29%), of which most patients received PPV with SO or gas tamponade and the rate of anatomic success was 89% (95%CI 85%-93%). Conclusion: CMVR is a common opportunistic infection with diverse clinical features in AIDS patients, preponderant in those who are male, homosexual, or with CD4+ T-cells <50 cells/μL. Current therapies for CMVR and CMVR-related RD were shown to be effective. Early detection and routine ophthalmic screening should be promoted in AIDS patients.